2019
DOI: 10.1101/711887
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacterially produced GABA protects neurons from degeneration

Abstract: Caenorhabditis elegans and its cognate bacterial diet comprise a reliable, widespread model to study diet and microbiota effects on host physiology. Nonetheless, how diet influences the rate at which neurons die remains largely unknown. A number of models have been used in C. elegans as surrogates for neurodegeneration. One of these is a C. elegans strain expressing a neurotoxic allele of the MEC-4(d) DEG/ENaC channel which causes the progressive degeneration of the touch receptor neurons (TRNs). Using such mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…It has been previously shown that diet may promote proteostasis and lifespan and protect from neurodegeneration in C. elegans (1,2,35,36). The transcriptional responses of C. elegans highly depends on the bacterial diet and different diets direct unique transcriptional signatures (2,37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously shown that diet may promote proteostasis and lifespan and protect from neurodegeneration in C. elegans (1,2,35,36). The transcriptional responses of C. elegans highly depends on the bacterial diet and different diets direct unique transcriptional signatures (2,37).…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains unclear what combination of nutrients is most beneficial. Over the years, C. elegans has been proven to be an important and reliable model for nutrient-dependent health-and lifespan studies with major discoveries being confirmed across species (1)(2)(3)(4)(5). The influence of dietary restriction on longevity was first assessed in C. elegans and is now widely accepted for mammals and even humans (3,(6)(7)(8).…”
Section: Main Text: Introductionmentioning
confidence: 99%